Women Receiving Massive Transfusion Due to Postpartum Hemorrhage: A Comparison Over Time Between 2 Nationwide Cohort Studies. Issue 2 (June 2020) - Ramler, P.I.; van den Akker, T.; Henriquez, D.D.C.A.; Zwart, J.J.; van Roosmalen, J.; van Lith, J.M.M.; van der Bom, J.; Paul, I.
Abstract : ( Acta Obstet Gynecol Scand . 2019;98:795–804) Postpartum hemorrhage (PPH) is on the rise in high-income countries. When PPH requires massive transfusion there is an increased risk of maternal morbidity and the need for hysterectomy. The aim of this study was to evaluate the incidence of PPH requiring massive transfusion in the Netherlands between 2011 and 2012 and compare this to previous data from 2004 to 2006. The study also assessed the causes of PPH and the management and outcome of women who received massive transfusions.